2015
DOI: 10.1007/s11121-015-0570-y
|View full text |Cite
|
Sign up to set email alerts
|

Early Academic Achievement Among American Low-Income Black Students from Immigrant and Non-Immigrant Families

Abstract: At least half of the well-documented achievement gap for low-income Black children is already present in kindergarten, due in part to limited opportunities for acquiring foundational skills necessary for school success. There is some evidence that low-income minority children from immigrant families have more positive outcomes than their non-immigrant counterparts, although little is known about how the immigrant paradox may manifest in young children. This study examines foundational school readiness skills (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 24 publications
2
14
0
4
Order By: Relevance
“…An emerging body of research suggests a protective effect of immigrant status against risk factors for later academic underachievement (Crosnoe & Turley, 2011). For example, in a subset of the sample considered in the current study, it was found that whereas lower pre‐K school readiness skills and lower pre‐K classroom quality predicted lower second grade math and reading achievement test scores for children of U.S.‐born parents, this predictive association was attenuated for children with at least one immigrant parent (Calzada et al, 2015). Thus, the current study also investigated whether the relation between EK and achievement differs for children of color from immigrant and non‐immigrant families.…”
Section: Ek and Learning: Theoretical Foundationsmentioning
confidence: 75%
See 2 more Smart Citations
“…An emerging body of research suggests a protective effect of immigrant status against risk factors for later academic underachievement (Crosnoe & Turley, 2011). For example, in a subset of the sample considered in the current study, it was found that whereas lower pre‐K school readiness skills and lower pre‐K classroom quality predicted lower second grade math and reading achievement test scores for children of U.S.‐born parents, this predictive association was attenuated for children with at least one immigrant parent (Calzada et al, 2015). Thus, the current study also investigated whether the relation between EK and achievement differs for children of color from immigrant and non‐immigrant families.…”
Section: Ek and Learning: Theoretical Foundationsmentioning
confidence: 75%
“…Finally, in examining differences between children from immigrant and non‐immigrant families, this study built on theory and prior research which suggests that pathways from early skills to achievement may differ for children from immigrant and non‐immigrant families (Calzada et al, 2015; Ogbu & Simons, 1998). Results suggest that relations of pre‐K EK to math achievement in kindergarten and second grade were weaker among children from immigrant families than among children from non‐immigrant families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the age of two, children of black immigrants scored lower on a test of cognitive functioning compared to many of their peer groups. Black children of immigrants achieved more in reading and math, outperforming black children of US-born parents and Latino children from immigrant and non-immigrant families (Calzada et al, 2015).…”
Section: Immigrationmentioning
confidence: 91%
“…Immigrant status is an important factor to consider in regards to understanding achievement among minority groups (Calzada, et al, 2015). There is a vast growing portion of the United States population since the year 2000.…”
Section: Immigrationmentioning
confidence: 99%